Perceval Sutureless valves in isolated and concomitant AVR procedures: an economic model shows overall decrease of costs for isolated or combined operations - Pradelli, Lorenzo; Zaniolo, Orietta (Farmeconomia. Health economics and therapeutic pathways, 2012)
BACKGROUND: aortic valve replacement (AVR) the most common heart valve operation, accounts for a majority of all valve surgery performed in the elderly. The Perceval S (P) is a new aortic valve which is implanted without suturing, which causes a significant reduction in cross-clamping times (CCTs), and makes valve implantation easier and faster thanks to its collapsed profile. These features potentially allow the pool of operable patients to be expanded, even with minimally invasive surgery in isolated AVRs. AIM: to predict costs and outcomes of AVR procedures associated with this new valve in 4 European countries (Italy, France, Germany, and UK), as compared to traditional (T) valve implants, from the cost perspective of the hospital. METHOD: a probabilistic, patient-level simulation model was fully coded in WinBugs, permitting a seamless integration of parameter estimation and outcomes prediction, which was entirely based on the associated CCTs and on the surgical technique (mini-invasive [MiS] vs. full sternotomy [FS]), through published correlations. Unit cost were retrieved from official and literature sources for all countries. Besides the incorporated probabilistic sensitivity analysis, a series of deterministic sensitivity analyses was performed. RESULTS: the model predicts the use of the Perceval S valve to be associated with less complications and with savings (valve cost excluded), mainly related to a reduction in surgery costs and ICU/hospital bed days. These savings range from € 3,600 (Italy) to £ 3,900 (UK) for PFS in isolated AVRs and from about € 6,000 (Italy) to £ 6,700 (UK) for PMiS in isolated AVRs, and for PFS in concomitants. Extensive sensitivity analyses confirm the robustness of such findings. CONCLUSIONS: the results of the present analysis indicate that the hospital acquisition cost difference between the new sutureless Perceval S valve and traditional valves is offset by important savings in other cost items.